Heritage, Tourism, and Race The Other Side of Leisure - Jackson, Antoinette T (Heritage, Tourism, and Community, 2020)
Heritage, Tourism, and Race views heritage and leisure tourism in the Americas through the lens of race, and is especially concerned with redressing gaps in recognizing and critically accounting for African Americans as an underrepresented community in leisure. Fostering critical public discussions about heritage, travel, tourism, leisure, and race, Jackson addresses the underrepresentation of African American leisure experiences and links Black experiences in this area to discussions of race, place, spatial imaginaries, and issues of segregation and social control explored in the fields of geography, architecture, and the law. Most importantly, the book emphasizes the importance of shifting public dialogue from a singular focus on those groups who are disadvantaged within a system of racial hierarchy, to those actors and institutions exerting power over racialized others through practices of exclusion. Heritage, Tourism, and Race will be invaluable reading for academics and students engaged in the study of museums, as well as architecture, anthropology, public history, and a range of other disciplines. It will also be of interest to museum and heritage professionals and those studying the construction and control of space and how this affects and reveals the narratives of marginalized communities.